Dimensi politik hukum dalam perkembangan ekonomi Islam di Indonesia - Bambang Iswanto (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2014)
This study aims to describe the history of recent Islamic economic development in the correlation to politics as a sought to formulated some Islamic economic laws. This qualitative study is an exploratory- analysis. It intended to analyze the position of Islamic economic in Indonesian’s system of law, so it will found the clear description of the implementation of Islamic economic laws in Indonesia. It is a library research. The study found that it is important to found the frame of the development of the products of Islamic economic law at the both period; i.e. New Order and Reformation Era. The concept of Islamic economy is still dominated by the application of Islamic principles in the areas of finance, especially banking. This dominance is not supposed to leave the Islamic economic instruments. In this respect, it associated with the political and legal product, then all the aspects and the Islamic economic instruments should be viewed comprehensively. Tulisan ini akan menguraikan mengenai sejarah ekonomi Islam modern dan keterkaitannya dengan politik dalam upaya merumuskan berbagai hukum ekonomi Islam. Penelitian kualitatif ini merupakan studi exploratory-analysis. Pendekatan ini dimaksudkan untuk menganalisis posisi ekonomi Islam dalam tata hukum Indonesia sehingga akan dapat diperoleh gambaran bagaimana bentuk implementasi ekonomi Islam di Indonesia. Penelitian kepustakaan ini menemukan urgensi untuk menemukan kerangka pengembangan produk hukum ekonomi Islam pada dua periode yang ada yaitu Orde Baru dan Era Reformasi. Konsep ekonomi Islam masih didominasi dengan penerapan prinsip Islam dalam bidang keuangan terutama perbankan. Dominasi ini tidak seharusnya melupakan instrumen ekonomi Islam lainnya karena jika dikaitkan dengan politik dan produk hukum, maka semua aspek dan instrumen ekonomi Islam tersebut harus bisa dilihat secara komprehensif.